Short-range order localizing diffusion in multi-principal element alloys. (15th March 2022) - Xing, Bin; Wang, Xinyi; Bowman, William J.; Cao, Penghui
Abstract: The impact of chemical short-range order (SRO) on diffusion is computationally studied and theoretically analyzed in two classes of multi-principal elements alloys, fcc CrCoNi and bcc MoNbTa. We find the presence of SRO considerably reduces and localizes vacancy-mediated diffusion. The diffusivity reduction is induced by an increase of migration barrier (decreasing jump frequency) and enhanced diffusion correlation that lowers the effectiveness of atomic jumps. By sampling the diffusion pathways and associated energy barriers, a picture of SRO-stretched potential energy landscape is conceived that elucidates an increasing backward jumps and vacancy trapping effect stemming from chemical ordering. The results imply controlling the ordering in chemistry can act as a potential approach for manipulating diffusional behaviors in multi-principal elements alloys. Graphical abstract: Image, graphical abstract